Institutional framework of public-private partnership development in Russia - Elena Nikolaevna Sidorova; Denis Aleksandrovich Tatarkin (Экономика региона, 2011)
The authors proceed from the thesis that the interaction between business and government is essential for the development of each state. This paper investigates the institutional framework of public-private partnership (PPP) in the Russian Federation. Based on the assessment of regulations functioning in Russia, it is concluded that, despite a number of legislative acts designed to regulate the scope of partnerships between the public and the private sector, due to the limited range of the issues and the lack of essential problems range studied, the question of legislative support to the PPP is not resolved. The role of public institutions in the development of interaction between government and business is shown. Based on the analysis of a large factual material, the institutions of PPP development are evaluated: the Investment Fund of the Russian Federation, state corporations, venture innovation funds and special economic zones. This paper states that for each country and region it is essential to identify the priority sectors of public-private partnership.